Iris Murdoch, or What It Means To Be A Serious Philosopher - Altorf, Marije (Daimon Revista Internacional de Filosofia, 2013)
The last few years have seen a growing interest in the philosophical work of Iris Murdoch. Where the interest in her literary work started early in her career, with the first monograph published in 1965, the first monograph on her philosophical work did not appear until 1996. It is now clear that this first work was not a one-off, but the start of a new area of research